Governor's Palace - (:unkn) unknown (Waterman, The Hatter, Clothier and Outfitter, Trinidad, 2009)
A picture of the Government House which was the residence to the Governors of Trinidad and Tobago from 1803 until 1976 when Trinidad and Tobago became a republic and the house was subsequently designated "The President's House". The postcard is addressed to Leo Kowchajki, Brooklyn, New York. Affixed to the postcard is a Trinidad and Tobago 1 penny stamp, postmarked March 3, 1919.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; 1919; Architecture--Trinidad and Tobago; President's House, The